2019
DOI: 10.1016/j.bandl.2019.104694
|View full text |Cite
|
Sign up to set email alerts
|

Shared premotor activity in spoken and written communication

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 130 publications
(195 reference statements)
0
5
0
Order By: Relevance
“…The SMA is involved in movement control; its activation is reliably observed in writing tasks but its contribution is considered non‐specific (Palmis et al, 2019; Purcell, Napoliello, et al, 2011; Rapp & Dufor, 2011; Rapp et al, 2016). More generally, it is often mobilized in language production tasks (Longcamp et al, 2019). Its stronger activation in expert adults is consistent with studies showing its critical role in coordination with complex and overlearned movements (Gerloff, 1997; Goldberg, 1985; Toni et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The SMA is involved in movement control; its activation is reliably observed in writing tasks but its contribution is considered non‐specific (Palmis et al, 2019; Purcell, Napoliello, et al, 2011; Rapp & Dufor, 2011; Rapp et al, 2016). More generally, it is often mobilized in language production tasks (Longcamp et al, 2019). Its stronger activation in expert adults is consistent with studies showing its critical role in coordination with complex and overlearned movements (Gerloff, 1997; Goldberg, 1985; Toni et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has reported that enhanced right FG activity during a reading task is associated with reading gain in English-speaking children who struggle with reading (Nugiel et al, 2019 ). In addition, the left PrCG is involved in handwriting (Longcamp et al, 2019 ; Roux et al, 2009 ) and Japanese children learn to read and write Kanji by intensive handwriting repetition (Naka and Naoi, 1995 ). These results suggest that the right FG network might be related to visually demanding Kanji reading and less involved in the phonological and automatic processing required for Hiragana in TD children.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, this hypothesis has not been tested, meaning that no one has compared in the same subjects the neural pathways underlying speech (i.e., laryngeal movements) and dance movements (e.g., rhythmic arm movements), although a cross-studies' comparison points to an overlap of several of the regions controlling body movements in the primary motor cortex with the regions that control laryngeal movements in the primary motor cortex [24][25][26] . Further, dance has been found to increase network connectivity between the basal ganglia and premotor cortices 27 , with both regions being co-activated during speech 28,29 . To address this question, in our control tasks, we had our dancers produce speech and speech-like vocalizations (e.g., Jabberwocky words), as well as other non-speech vocalizations (e.g., sneeze, laughter, yawn), with the aim to compare their EEG patterns during laryngeal movements vs. movements of other body parts.…”
Section: Motor Hypothesis Of Vocal Learningmentioning
confidence: 99%
“…In humans, this hypothesis has not been tested, meaning that no one has compared in the same subjects the neural pathways underlying speech (i.e., laryngeal movements) and dance movements (e.g., rhythmic arm movements), although a cross-studies' comparison points to an overlap of several of the regions controlling body movements in the primary motor cortex with the regions that control laryngeal movements in the primary motor cortex (28)(29)(30). Further, dance has been found to increase network connectivity between the basal ganglia and premotor cortices (31), with both regions being coactivated during speech (32,33).…”
Section: B) Motor Hypothesis Of Vocal Learningmentioning
confidence: 99%